Enhancement of biodiesel production from soybean oil by electric field and its chemical kinetics - Piyaphong Yongphet (2020)
© 2020 The mass transfer limitation of conventional transesterification reaction is the reason for reaction time extension and separation prolongation. In the present work, an electric field was used to overcome the mass transfer limit through barrier discharge. The ring electrode attached to a glass cylinder and the rod electrode inside the glass cylinder was applied to reduce surface tension between methanol and soybean oil, to speed up the reaction process. The 220 V AC was provided to the variable voltage transformer to create a high voltage electric field and accelerate the transesterification reaction. The results show that the optimal conditions for the transesterification process were: 1% catalyst, 6:1 M ratio of methanol/oil, agitation speed of 600 rpm, the reaction time of 30 min at different reaction temperatures (25 °C–60 °C). The maximum yield obtained after purification was 95.72 %. In addition, the kinetic study of the transesterification reaction was adequately explored in terms of a -pseudo-first-order reaction, with an activation energy of 14.35 kJ⋅ mol−1 and a frequency factor of 0.38 s−1. The electric field turns out to enhance the transesterification process with faster reaction time efficiently, which reduces energy consumption.